A Mechanistic Understanding of Processing Additive‐Induced Efficiency Enhancement in Bulk Heterojunction Organic Solar Cells. (31st October 2013) - Schmidt, Kristin; Tassone, Christopher J.; Niskala, Jeremy R.; Yiu, Alan T.; Lee, Olivia P.; Weiss, Thomas M.; Wang, Cheng; Fréchet, Jean M. J.; Beaujuge, Pierre M.; Toney, Michael F.
<x xml:space="preserve">Abstract</x> The addition of processing additives is a widely used approach to increase power conversion efficiencies for many organic solar cells. We present how additives change the polymer conformation in the casting solution leading to a more intermixed phase‐segregated network structure of the active layer which in turn results in a 5‐fold enhancement in efficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>